The Effect Of Principal Transformational Leadership And Teacher Digital Literacy On State High School Teacher Professionalism - Novi Susanti; Hasnah Faizah; Mangatur Sinaga; ijayani ijayani (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to determine the influence of variables (1) the principal's transformational leadership on teacher professionalism, (2) teacher digital literacy on teacher professionalism, and (3) principal transformational leadership and teacher digital literacy together on teacher professionalism. The research population was 175 public high school teachers in Pinggir District, Bengkalis Regency, and 122 people as the research sample. This research approach is a quantitative approach with data collection carried out through the distribution of questionnaires as a research instrument. Data analysis used is descriptive analysis, inferential statistical analysis, and hypothesis testing. The instrument reliability coefficient was calculated using the alpha-Cronbach formula. The results showed that there was a positive and significant influence between the principal's transformational leadership on teacher professionalism of 51.40%, and there was a positive and significant influence between teacher digital literacy on teacher professionalism of 55.80%. Meanwhile, together there is a positive and significant influence of the principal's transformational leadership and teacher's digital literacy on teacher professionalism of 53.50%.